Answer:
[tex]\left(6-v-25\right)-\left(7+\left(-4\right)\right)=-v-22[/tex]
Step-by-step explanation:
Considering the expression
[tex]\left(6-v-25\right)\:-\:\left(7+-4\right)[/tex]
[tex]\left(6-v-25\right)-\left(7+\left(-4\right)\right)[/tex]
[tex]\mathrm{Remove\:parentheses}:\quad \left(a\right)=a[/tex]
[tex]6-v-25-\left(7-4\right)[/tex]
[tex]\mathrm{Subtract\:the\:numbers:}\:7-4=3[/tex]
[tex]6-v-25-3[/tex]
[tex]\mathrm{Group\:like\:terms}[/tex]
[tex]-v+6-25-3[/tex]
[tex]\mathrm{Add/Subtract\:the\:numbers:}\:6-25-3=-22[/tex]
[tex]-v-22[/tex]
Therefore,
[tex]\left(6-v-25\right)-\left(7+\left(-4\right)\right)=-v-22[/tex]